A multidisciplinary approach to the teacher's guiding role in the community and educational context (Educational Knowledge, 2020)
The educational setting, as a place where diverse social and cultural practices converge, has become a turbulent and controversial space, rife with problematic situations that warrant the use of group and individualized intervention strategies such as: promoting social skills, teamwork, managing emotional competencies, and peaceful conflict resolution. All these strategies foster the right conditions for students and other educational stakeholders to resolve—either independently or with the cooperation of others—the personal, emotional, affective, educational, and social conflicts that hinder the consolidation of optimal and healthy lifestyles.In light of the above, this article discusses the teacher's guiding role within the community and educational context, from a multidisciplinary perspective that integrates the aspects, contributions, and concrete actions that their work offers to holistic human development and the transformation of educational and community settings.
Keywords: Community orientation; social participation; group cohesion; skills; competences